Hubungan Dukungan Sosial dengan Perilaku Manajemen Diri pada Pasien Hipertensi di Puskesmas Pandak I Bantul DI. Yogyakarta - Umi Khomsatun; Ike Wuri Winahyu Sari (Jurnal Keperawatan Klinis dan Komunitas (Clinical and Community Nursing Journal), 2021)
Background: Hypertension is a chronic disease which needs good self management. One of the factors influencing self-management behavior is social support. There are still limited number of studies which examine the correlation between social support and self-management behavior in patients with hypertension, especially focusing on certain behaviors such as the adherence on taking medicine, food intake, physical activities, smoking, maintaining the body weight, and avoiding alcohol consumption.Objective: To identify the correlation between social support and self-management behavior in patient with hypertension located in Puskesmas Pandak I Bantul.Methods: This research design used a descriptive correlative design with cross-sectional approach. The sample were 47 respondents who were selected using purposive sampling technique. The data collection used questionnaire of Chronic Illness Resources Survey (CIRS) and Hypertension Self-Care Activity Level Effects (H-SCALE) which were valid and reliable. The data was analysed using Pearson Corelation and Spearman Rank Test analysis to identify the relationship of social support to self management behavior in patients with hypertension.Results: The result showed that the social support had a significant correlation with self-management behavior in the food intake domain (r= 0,336; p= 0,021) and in the domain of body weight management (r= 0,392; p= 0,006). Meanwhile, the social support did not have a significant correlation with self-management behaviour in the domains of the adherence on taking medicine (p= 0,351), physical activity (p= 0,974), and smoking (p= 0,908).Conclusion: There is a significant correlation between social support and self-management behavior in the domains of food intake and body weight management. Nurses can provide health promotion related to self management as well as the increased of social support in patients with hypertension. ABSTRAKLatar Belakang: Hipertensi merupakan penyakit kronik yang memerlukan manajemen diri yang baik. Salah satu faktor yang memengaruhi perilaku manajemen diri adalah adanya dukungan sosial. Namun, penelitian terkait hubungan dukungan sosial dengan perilaku manajemen diri pada pasien hipertensi dengan menggali aspek tiap domain seperti kepatuhan minum obat, asupan makanan, aktivitas fisik, merokok, menjaga berat badan, dan kepatuhan tidak mengkonsumsi alkohol, masih sangat terbatas.Tujuan: Penelitian ini bertujuan untuk mengetahui hubungan dukungan sosial dengan perilaku manajemen diri pada pasien hipertensi di Puskesmas Pandak I Bantul.Metode: Rancangan enelitian ini adalah deskriptif korelatif dengan pendekatan cross sectional. Sebanyak 47 responden dipilih dengan teknik purposive sampling. Pengumpulan data menggunakan kuesioner Chronic Illness Resources Survey (CIRS) dan Hypertension Self-Care Activity Level Effects (H-SCALE) yang telah valid dan reliabel. Analisis data Uji Pearson Correlation dan Spearman Rank digunakan untuk melihat hubungan dukungan sosial dengan perilaku manajemen diri pada pasien hipertensi.Hasil: Hasil penelitian menunjukkan bahwa dukungan sosial memiliki hubungan yang signifikan dengan perilaku manajemen diri pada domain asupan makanan (r= 0,336; p= 0,021) dan domain manajemen berat badan (r= 0,392; p= 0,006). Sementara dukungan sosial tidak memiliki hubungan yang signifikan dengan perilaku manajemen diri pada domain kepatuhan minum obat (p= 0,351), domain aktivitas fisik (p= 0,974), dan domain merokok (p= 0,908).Kesimpulan: Ada hubungan yang bermakna antara dukungan sosial dengan perilaku manajemen diri pada domain asupan makanan dan berat badan. Perawat dapat memberikan promosi kesehatan terkait management diri serta peningkatan dukungan sosial pada pasien hipertensi.